SARS-COV-2 INFECTION AND ITS SYMPTOMS AMONG COVID-19 VACCINATED AND UNVACCINATED HEALTH-CARE WORKERS - Maurya, Vinod Kumar; Shukla, Surabhi; Bora, Archana; Rathore, Laxmi (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: India’s national coronavirus disease 2019 (COVID-19) vaccination programs started during January 2021 and prioritized health-care workers (HCWs). In this study, we are attempting to measure post-vaccination product-specific (ChAdOx1_nCoV-19/COVISHIELD) COVID-19 vaccine effectiveness among vaccinated hospital HCWs and also to assess symptoms in HCWs with reverse transcription-polymerase chain reaction (RT-PCR) confirmed severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection. Methods: This is an online web-based cross-sectional study conducted in June 2021 among vaccinated HCWs, comparing SARS-CoV-2 incidence and symptoms. In this study, demographic data such as age, gender, and profession were collected. Other data collected were vaccination status at the time of infection, the gap between COVID-19 positivity and vaccination, symptoms, hospitalization, time to recovery, and previous positive history before vaccination. Results: A total of 1685 HCWs were vaccinated with the COVISHIELD vaccine from January 16 to March 18, 2021. Out of 1685 HCWs, 82 (4.8%) were tested positive by RT-PCR after vaccination. Out of 82 positive HCWs, 84% experienced mild symptoms, 12.2% experienced moderate symptoms, and 3.7% had severe manifestations leading to hospitalization. Among these positive HCWs, 25.6% recovered within 7 days, 35.3% recovered in 7–10 days, 15.8% recovered in 11–14 days, and 23.1% recovered after 2 weeks from the 1st day of experiencing symptoms. Conclusion: Although COVID-19 vaccination by COVISHIELD may not fully prevent from infection by SARS-CoV-2 or its different variants, majority of positive cases present with asymptomatic/mild symptoms. Post-vaccination-positive cases may also present with severe symptoms and require hospitalization.